An assessment of early colonisation of implant-abutment metal surfaces by single species and co-cultured bacterial periodontal pathogens. (October 2016) - Jordan, Rachael P.C.; Marsh, Lucy; Ayre, Wayne Nishio; Jones, Quentin; Parkes, Matthew; Austin, Bryan; Sloan, Alastair J.; Waddington, Rachel J.
Abstract: Objective: Numerous studies have proposed that smooth metal surfaces reduce initial bacterial attachment in the establishment of an early biofilm formation. However, these studies have largely examined single bacterial species, which are not always relevant as pathogens identified as initiators of inflammatory peri -implantitis. This study investigated the adherence of four periodontally-relevant bacterial species to implant and abutment surfaces in current clinical use. Methods: Discs of polished cobalt chromium (CoCr-polished) and milled titanium (Ti-milled), representing two clinically relevant surfaces, were prepared and surfaces were characterised. Bacterial species Porphyromonas gingivalis, Fusobacterium nucleatum, Prevotella intermedia and Aggregatibacter actinomycetemcomitans were cultured to mid-log or stationary growth phase. Co-cultures of P. gingivalis, F. nucleatum and P. gingivalis, F. nucleatum, Pr. intermedia were similarly prepared. Bacteria were inoculated onto discs for 2 h, stained with a live/dead fluorescent stain and percentage bacterial coverage was calculated by confocal microscopy and image analysis. Results: CoCr-polished discs had smooth surfaces with gentle valley structures, whilst Ti-milled discs had sharp edged peaks. Both discs demonstrated a partial wetting ability capable of initiating bacterial adhesion. P. gingivalis, F. nucleatum and co-cultures, at both mid-log and stationary concentrations, demonstrated equally high coverage of both the smooth CoCr-polished and the rougher Ti-milled metal surfaces. Pr. intermedia and A. actinomycetemcomitans demonstrated lower surface coverage which was slightly higher for Ti-milled. Conclusion: Variability was noted in the adherence potential for the respective periodontal pathogens examined. Particularly high adherence was noted for P. gingivalis and F. nucleatum, despite the manufacture of a smooth surface. Clinical significance: Both surfaces studied may be used at implant-abutment junctions and both possess an ability to establish a bacterial biofilm containing a periodontally-relevant species. These surfaces are thus able to facilitate the apical migration of bacteria associated with peri -implantitis.